English Major Students Self-Concept Perspective on Viewing Translator as a Profession - Husain, Dahlia; Bahar, Bahar (English Department, Universitas Negeri Surabaya, 2020)
This paper reports on a research conducted to explore English major students view on becoming a translator as their future profession. The focus is divided into 3 main concerns 1) do the students consider translator as their profession after graduation? 2)do the students think they are equipped with enough knowledge on becoming a translator? 3)what elements should the English Department provide to support their career choice?. These concerns were presented in a perceptional questionnaire as the main data collection technique that aims to find out whether the students of English Literature as the University of Muhammadiyah Gorontalo would consider translator as their career. This is a qualitative research with total sampling as the technique of data collection. The subject of the research were 20 students of 6th semester majoring in English Literature at Muhammadiyah University of Gorontalo. The result of the study showed that the students have moderate consideration on choosing a career path of translation. There are several reason behind such thoughts, one of which is they do not think they qualified for becoming a professional translator or choosing the line of work as their future profession. Moreover, they think that the faculty can provide more classes on translation to build both their skills and their confidence on becoming future translators.